STRATEGI PENANGGULANGAN KEMISKINAN DI KOTA BATAM - Wahyuniati, Diana; Abbas, Azhar (SCIENTIA JOURNAL, 2020)
Poverty is one of the problems facing the city of Batam. Where the poverty reduction strategies that have been implemented by the Social Service and Community Empowerment of Batam City so far have not been effective in reducing the amount of poverty that exists. One of the programs carried out by the Batam city government is Non-Cash Food Assistance and Uninhabitable Home Rehab. In connection with the problem under study, that is to find out alternative strategies that can be used by the government to tackle poverty in Batam. The method used is a SWOT analysis in which to find out what are the strengths, weaknesses, oppurtunities, and threats of the Batam city poverty reduction strategy through structured interviews with questions prepared earlier. As the informant, namely the section head for handling the poor, the Social and Empowerment Office and the community receiving social assistance. The results of the study prove that poverty reduction strategies implemented by the Office of Social and Community Empowerment have not been able to reduce poverty. This is because the program is only to help meet the basic needs of the poor. Based on the results of research suggestions for the Social Service and Community Empowerment as an agency that handles poverty issues, to create programs that encourage the productivity of the poor so they can move from poverty.